A CONCEPTUAL APPROACH TO THE DEVELOPMENT OF THE DIDACTIC-METHODICAL COMPETENCE OF THE FUTURE PRIMARY SCHOOL TEACHER - Badalov Kamoliddin; Kholmuroda Nasiba Kholiqovna (Scholar Express Journal, 2023)
This article contains necessary information for students of higher educational institutions and teachers of primary education. This article discusses conceptual approaches to the development of the didactic-methodical competence of the future primary school teacher
Keywords: educational system; psychological and pedagogical sciences